Liberalism and Islam Practical Reconciliation between the Liberal State and Shiite Muslims - Haidar, H. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2008)
This book examines the possibility of reconciliation between liberalism and Shiite Islam. By examining two key liberal theories, this book shows that secular liberalism is not justifiable in the view of Shiite Islamic thought.